"A Hypothesis on Armenian Notation ". - Aloyan Էրիկ Վարդանի (Musical Armenia, 2024)
The invention of the Armenian Notation in the early XIX century by a number of musicians from Constantinople (Hambartsoum Limonjian, Fr. Minas Bzhshkian, Hagob Chelepi Tiuzian, Anton Amira Tiuzian) holds a significant place in the history of Armenian Music. Although the invention had a very specific and important purpose, it also brought up a number of problems: what the reasons of the creation of the system were, who the inventors were, how transpositions from the mentioned system to European notation should be done. In the present article an attempt has been made by the authors to bring together the available information and to propose hypothesis about the mentioned disagreements.